Can China’s New Infrastructure Promote Urban–Rural Integrated Development? Evidence from 31 Chinese Provinces - Yaolong Li; Xiaojie Ma; Yang Liu; Fanglei Zhong (Buildings)
Whether and how new infrastructure (NI) promotes urban–rural integration (URI) remains crucial for addressing unbalanced urban–rural development. This study analyzes panel data from 31 provincial-level administrative regions in China (2013–2022) to construct an evaluation index system for URI, encompassing economic, social, ecological, spatial, and demographic dimensions. Using the entropy method, the study quantifies the development level of NI and investigates its differential effects on URI. The empirical findings demonstrate that NI exhibits a significant positive effect on URI, with the strongest impact manifested in economic and spatial dimensions. The influence on social, ecological, and demographic aspects, while positive, is comparatively modest. Regional disparities and innovation investment levels contribute to the heterogeneous impact of NI. Moreover, the study reveals that industrial structure advancement serves as the transmission mechanism through which NI drives URI. The promotional effect becomes more pronounced after crossing both the double threshold of industrial structure upgrading and the single threshold of industrial structure rationalization. Based on these findings, the following policy recommendations are proposed to optimize the new infrastructure investment structure, promote deep integration with industrial structural adjustments, and implement new infrastructure construction in accordance with local conditions.